KEPASTIAN HUKUM PARA PIHAK DALAM JUAL BELI RUKO DIATAS TANAH HAK PENGELOLAAN - Kusnandar, Bimantara; Saleh, Moh (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
Land is a natural resource essential for the survival of mankind. The relationship between humans and land is more than just a place to live. Land is a place where humans live and thrive, and it is also a source for all the necessities of human life. Due to the importance of land for the survival of society, many problems arise in the sale and purchase of buildings whose land is located on land with Management Rights. The problem in this article is how the concept of legal certainty in the sale and purchase of land with Building Use Rights on land with Management Rights. The concept of legal certainty to protect consumers in the ownership of a building/land is not limited to the aspect of the Building Use Rights certificate for the owner but also includes, first, the aspect of the recommendation agreement to the Management Rights holder, which is the starting point. Second, the aspect of land control, which is the product point. After all requirements are met, the Building Use Rights certificate is issued on the Management Rights. If the three aspects above are met, there is legal certainty and the consequence is that consumers as building/land owners receive legal protection.